2013
DOI: 10.9745/ghsp-d-12-00004
|View full text |Cite
|
Sign up to set email alerts
|

GeneXpert for TB diagnosis: planned and purposeful implementation

Abstract: Xpert MTB/RIF is a major advance for TB diagnostics, especially for multidrug-resistant (MDR) TB and HIV-associated TB. But implementation concerns including cost, technical support requirements, and challenging demands of providing second-line TB drugs for diagnosed MDR-TB cases call for gradual, careful introduction based on country circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 4 publications
1
98
0
3
Order By: Relevance
“…However, cost of Xpert assay is more than smear microscopy; it requires a machine that currently costs US$17,000 and cartridges that cost US$9.98 for each test, in addition to human resource and other running costs [20]. Vassall et al, reported the cost for the Xpert test (including all costs, such as the cartridge, equipment, salaries) ranges from US$22.63 in India to US$27.55 in Uganda [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, cost of Xpert assay is more than smear microscopy; it requires a machine that currently costs US$17,000 and cartridges that cost US$9.98 for each test, in addition to human resource and other running costs [20]. Vassall et al, reported the cost for the Xpert test (including all costs, such as the cartridge, equipment, salaries) ranges from US$22.63 in India to US$27.55 in Uganda [21].…”
Section: Discussionmentioning
confidence: 99%
“…7 However, the right placement of Xpert machines in the laboratory requires careful consideration of available resources, national capacity building and accessibility of diagnostic testing. 8 …”
mentioning
confidence: 99%
“…However, it is expensive and requires moderate levels of infrastructure (such as an airconditioned room and reliable power supplies). That may not be suitable for primary care centres [19]. The main limitation of GeneXprt MTB/RIF is that it cannot be reliably used to detect resistance to first-line [13,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Including automatic reading of tubes into the MGIT assay adds considerably to the costs and has advantage only in settings where there is a high flow of specimens through the laboratory. All of these assays, however, require safe facilities and highly skilled personnel, suggesting they are best placed at tertiary levels of care [1,19]. Solid LJ-DST is still regarded as the standard by which to compare the reliability of other tests [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation